Hubungan Kepemimpinan Situasional, Motivasi Kerja, dan Iklim Kerja dengan Kinerja Guru - Suandi, I Wayan; Lasmawan, Wayan; Natajaya, Nyoman (Universitas Pendidikan Ganesha, 2017)
This research aimed to investigate: 1) the relationship between situational leadership and teachers’ performance, 2) the relationship between working motivation and teachers’ performance, 3) the relationship between working climate and teachers’ performance, 4) The relationship among situational leadership, working motivation, and working climate on the performance of teachers of public junior high school. The population is 98. This research used census study with the design of expost-facto. The data were collected using the questionnaire. The data were analyzed using multiple regressions. The results of the research show that there is a positive and significant relationship between: 1) situational leadership and teachers’ performance with the contribution of 39,5%, 2) working motivation and teachers’ performance with the contribution of 69.1%, 3) working climate and teachers’ performance with the contribution of 55.0%, 4) situational leadership, working motivation, and working climate on the performance of teachers of public junior high school in Negara Subdistric with the coantribution of 77.1%.